2021
DOI: 10.1002/app.51838
|View full text |Cite
|
Sign up to set email alerts
|

High pressure homogenization of graphene and carbon nanotube for thermal conductive polyethylene composite with a low filler content

Abstract: Thermal conductive polymer composite pipes have been used to replace metal pipes that are easy to be corroded. However, the low thermal conductivity of the matrix is the critical factor limiting their applications. Here, large‐size exfoliation of graphene and carbon nanotube (CNT) are proposed to prepare thermal‐conductive polyethylene nanocomposites with a low filler content. Expanded graphite and CNT are co‐dispersed by high pressure homogenizer in presence of polyvinyl pyrrolidone. Such a dispersion method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Correspondingly, HPH is suitable for use to directly produce a wide variety of dispersions and has been demonstrated as an effective technique for dispersing and potentially modifying nanomaterials (Azoubel and Magdassi, 2010;Li et al, 2019;Schlüter et al, 2014;Tölle et al, 2012). Many studies have reported successful use of HPH as a processing step to produce advanced materials such as graphene films and inks (Tölle et al, 2012), polymer composites incorporating nanomaterials for improved mechanical, thermal and electrical properties (Appel et al, 2012;Chatterjee et al, 2012;Clausi et al, 2020;Shayganpour et al, 2019;Wu et al, 2021;Xu et al, 2020), and nanofluids which will be discussed.…”
Section: Nanoscale Materials and Fluidsmentioning
confidence: 99%
“…Correspondingly, HPH is suitable for use to directly produce a wide variety of dispersions and has been demonstrated as an effective technique for dispersing and potentially modifying nanomaterials (Azoubel and Magdassi, 2010;Li et al, 2019;Schlüter et al, 2014;Tölle et al, 2012). Many studies have reported successful use of HPH as a processing step to produce advanced materials such as graphene films and inks (Tölle et al, 2012), polymer composites incorporating nanomaterials for improved mechanical, thermal and electrical properties (Appel et al, 2012;Chatterjee et al, 2012;Clausi et al, 2020;Shayganpour et al, 2019;Wu et al, 2021;Xu et al, 2020), and nanofluids which will be discussed.…”
Section: Nanoscale Materials and Fluidsmentioning
confidence: 99%
“…Nanocomposites with 5.22 wt.% MWCNT fillers reached a thermal conductivity of 1.2651 W m −1 K −1 , 3.94 times compared with the pure polyethylene. [ 16 ]…”
Section: Introductionmentioning
confidence: 99%
“…[15] Other important properties like thermal exchange play a significantly important role in the fields of chemical and thermal engineering for pipe and tubing fabrications. Jia et al [16] obtained polyethylene with low content of MWCNT, which after optimizing the composition showed thermal conductivity with enhanced mechanical properties. Nanocomposites with 5.22 wt.% MWCNT fillers reached a thermal conductivity of 1.2651 W m À1 K À1 , 3.94 times compared with the pure polyethylene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of fillers such as talc and carbon nanotube have effectively enhanced relevant thermo-mechanical properties of PE, which is particularly advantageous for pressure pipes applications. 8,9 These PE composites are also suitable for packaging of electronic utensils, 10,11 as the enhanced thermal conductivity allows for proper heat dissipation in such devices. In addition to improvements in thermal conductivity, higher dimensional stability can be achieved by filler incorporation, which can be particularly attractive for 3D-printing applications.…”
Section: Introductionmentioning
confidence: 99%